ChromaFit - Rohairry, Azwien Elisya; Masnaliz, Dhiya Qaisara; Noor Ibrahim, Noor Marlisa Zahra; Muhaimi, Siti Nur Aisyah (2025)
ChromaFit Sdn. Bhd. is an innovative smart clothing brand that combines fashion and technology by using biometric data—such as heart rate, skin temperature, and breathing patterns—to dynamically change garment colors according to the wearer’s emotional state. Designed for mental health support, sports performance, entertainment, and everyday use, ChromaFit promotes emotional regulation, self-awareness, empathy, and non-verbal communication. Stylish and user-centric, the smart apparel integrates lifestyle and emotional intelligence, empowering users to feel seen, understood, and confident. Positioned at the intersection of wearable tech and emotional well-being, ChromaFit aims to lead the emerging smart fashion industry with innovation that enhances human connection and mental wellness.